Indicators of energy metabolism in llamas (Lama glama) in the prepartum, postpartum and lactation transition period - Faustina Cayo-Rojas; Lindón Willy Mamani-Linares (Journal of the Selva Andina Animal Science)
Energy metabolism indicators allow determining the nutritional and metabolic condition and the energy imbalance that may be the cause of low fertility rates in llamas grazing on native pastures. In llamas, gestation is long, only one calf is born per year and the fertility rate is low. Therefore, measures must be taken to prevent miscarriages and give the offspring the best possible start in life. During the prepartum, postpartum and lactation transition period the decrease in dry matter intake coincides with the increase in nutrient demand due to the onset of lactation, which can lead to a negative energy balance, the enormous metabolic challenges during the transition period are related to the negative energy balance as a result of the mobilization of the body's energy reserves by increasing the concentration of non-esterified fatty acids and beta-hydroxybutyrate in the blood plasma. Camelids have higher blood glucose concentrations, lower plasma ketone body concentrations than domestic ruminants, a weak response to insulin and reduced cellular glucose uptake. The imbalance in metabolic adaptation mechanisms during the transition and lactation period interferes with body homeostasis, also predisposing to the development of ketosis. In addition, early postpartum is associated with a prolonged period of postpartum anestrus, delayed ovulation and poor reproductive outcomes.